Numerical and experimental assessment of a downdraft gasifier for electric power in Amazon using açaí seed (Euterpe oleracea Mart.) as a fuel - Itai, Y. (2015)
The Amazon region is characterized by communities isolated from the grid that currently are using Diesel engines to produce electricity and that have residual biomass energy potentials between 60 and 500 kW. In this scenario, gasification appears as an evident choice as far as energy generation is concerned. Other than wood, açaí seed is the biomass residue most wasted in the Pará State and its use in gasification systems is assessed in this study. With this purpose, a cylindrical bodied downdraft gasifier was designed, built and tested, and an equilibrium model implemented. The comparison of the simulation values with the experimental and numerical results of other authors show that they are in-line with the predictions of other equilibrium models. Also, they confirm that this kind of models is a fast and useful tool for a preliminary assessment of the applicability of a specific biomass gasification process for electricity production. Moreover, the deviation between the numerical and experimental results obtained in this study was lower around the equivalence ratio that optimizes the gasification process (in the 2.15-2.3 range). As far as biomass humidity is concerned, the producer gas calorific value and cold gas efficiency decreases with an increase in this parameter.